Design of Miniaturized Multiband Filters Using Zero Order Resonators for WLAN Applications. (9th March 2015) - Shafiee, Maryam; Chaychi Zadeh, Mohammad Amin; Oraizi, Homayoon
Abstract : The objective of this paper is to design miniaturized narrow- and dual-band filters for WLAN application using zero order resonators by the method of least squares. The miniaturization of the narrow-band filter is up to 70% and that of the dual-band filter is up to 64% compared to the available models in the literature. Two prototype models of the narrow-band and dual-band filters are fabricated and measured, which verify the proposed structure for the filter and its design by the presented method, using an equivalent circuit model.